Old age is associated with increased severity of complications in endoscopic biliary stone removal. Issue 4 (4th December 2013) - Nishikawa, Takao; Tsuyuguchi, Toshio; Sakai, Yuji; Sugiyama, Harutoshi; Sakamoto, Dai; Nakamura, Masato; Yokosuka, Osamu
<x xml:space="preserve">Abstract</x> Background and Aim Various techniques are required in endoscopic biliary stone removal. Because the presence of biliary stones is a benign disease, it is essential to minimize procedure‐related complications. Having a sound knowledge of the risk factors can help reduce the number and severity of complications. We determined the risk factors for complications in patients undergoing endoscopic biliary stone removal. Methods This was a retrospective observational cohort study. We analyzed 743 consecutive patients with biliary stones who were treated with endoscopic retrograde cholangiopancreatography and identified the independent risk factors for complications. Results Complications occurred in 66 patients (8.9%). Pancreatitis occurred in 26 patients (3.5%), cholangitis in 16 (2.2%), bleeding in 12 (1.6%) and other in 12 (1.6%). Independent risk factors for overall complications were multiple biliary stones (P = 0.0480) and anti‐thrombotic drugs (P = 0.0186).Independent risk factors for moderate or severe complications were old age (P = 0.0201), multiple biliary stones (P = 0.0300), anti‐thrombotic drugs (P = 0.0131), and cirrhosis of the liver (P = 0.0013). The respective risk factors for pancreatitis, cholangitis, and bleeding were precut technique (P = 0.0005), endoscopic mechanical lithotripsy (P = 0.0421), and both anti‐thrombotic drugs (P = 0.0228) and cirrhosis of the liver (P = 0.0115). Conclusions Old age was associated with a similar complication rate to younger age but increased the severity of complications following endoscopic biliary stone removal. Improved awareness of the severity of complications may be of benefit during periprocedural management. Further studies are warranted.